The Influence of Digitalization of Regional Financial Accounting System and Human Resource Competence on Government Agency Performance Accountability with Quality of Local Government Financial Statement as a Mediating Variable - Sri Wahyuni Zanra; Dinda Genta Wicara; Rama Fandrifal (Journal of Digital Business and Management, 2026)
The digitalization of regional financial governance through the Regional Government Information System (SIPD) has become a priority agenda in Indonesia's public financial reform, yet its success also depends on the competence of financial management human resources within each Regional Government Organization (OPD). This study aims to examine the effect of digitalization of regional financial Accounting System and human resource competence on government agency performance accountability, with the quality of local government financial statements as a mediating variable, in OPDs within the Rokan Hilir Regency Government. This study employs a quantitative approach with a causal-associative design. The population consists of financial management employees across all OPDs in Rokan Hilir Regency, with purposive sampling directed at Financial Administration Officers (PPK), treasurers, and accounting/reporting staff. Primary data will be collected through a 1-5 Likert-scale questionnaire and analyzed using Partial Least Square Structural Equation Modeling (SEM-PLS), with mediation tested through Variance Accounted For (VAF) and bootstrapping. This study is expected to provide empirical evidence on the role of accounting system digitalization and HR competence in improving financial statement quality and government performance accountability, and to serve as a policy input for the Rokan Hilir Regency Government in accelerating the digital transformation of regional financial management.